Epilepsy control during an epidemic: emerging approaches and a new management framework - Deng Chen; Lina Zhu; Xin Lin; Zhen Hong; Shichuo Li; Ling Liu; Dong Zhou (Acta Epileptologica, 2020)
Abstract Epidemics are a big threat to world health. The ongoing pandemic of corona virus disease 2019 (COVID-19) has caused a series of challenges to public health. One such challenge is the management of chronic diseases such as epilepsy during an epidemic event. Studies on this topic are rather limited and the related medical practice is full of uncertainty. Here we review recent development of potential approaches for epilepsy control during an epidemic and propose a new three-level management framework to address these challenges.